2006
DOI: 10.1111/j.1462-2920.2006.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of quorum sensing mediated developmental traits in the resistance of Serratia marcescens biofilms against protozoan grazing

Abstract: Resistance against protozoan grazers is a crucial factor that is important for the survival of many bacteria in their natural environment. However, the basis of resistance to protozoans and how resistance factors are regulated is poorly understood. In part, resistance may be due to biofilm formation, which is known to protect bacteria from environmental stress conditions. The ubiquitous organism Serratia marcescens uses quorum sensing (QS) control to regulate virulence factor expression and biofilm formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 29 publications
2
58
1
Order By: Relevance
“…Further, Chung and Chen (2008) found that the inactivation of Escherichia coli by chitosan occurs via a two-step sequential mechanism: initial separation of the cell wall from its cell membrane, followed by destruction of the cell membrane. Hejazi and Falkiner (1997) demonstrated that S. marcescens mannose-dependent fimbriae can adhere to biological surfaces and form biofilms, which are aggregations of bacteria and extracellular secretions (Queck et al, 2006). Fimbriae are among the virulent cell-surface structures of S. marcescens which contain the adhesins mediating adherence to eukaryotic cell surfaces, via recognition of specific carbohydrate moieties on the host cell surface glycoconjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Chung and Chen (2008) found that the inactivation of Escherichia coli by chitosan occurs via a two-step sequential mechanism: initial separation of the cell wall from its cell membrane, followed by destruction of the cell membrane. Hejazi and Falkiner (1997) demonstrated that S. marcescens mannose-dependent fimbriae can adhere to biological surfaces and form biofilms, which are aggregations of bacteria and extracellular secretions (Queck et al, 2006). Fimbriae are among the virulent cell-surface structures of S. marcescens which contain the adhesins mediating adherence to eukaryotic cell surfaces, via recognition of specific carbohydrate moieties on the host cell surface glycoconjugates.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, the cross-domain communication by AHLs between bacteria in biofilms and spores of green alga Ulva indicated a direct function of AHLs in biofouling development (Joint et al, 2002). Furthermore, it was reported that QS mediated developmental traits in the resistance of Serratia marcescens biofilms against protozoan grazing (Queck et al, 2006). The potential roles of AHLs in marine environments remain to be explored.…”
Section: Dynamics Of Ahl-producing Bacteria During Subtidal Biofilm Fmentioning
confidence: 99%
“…As a global regulation signals for bacterial activities, AHLs may affect not only the biofilm composition, but also the consequence of biofilm activities in environment such as biofouling development, nitrogen fixation, sulfate reduction, the degradation of organic matter and, moreover, provide shelter for certain bacteria (Costerton et al, 1995;Qian, 1999;Decho, 2000;Valle et al, 2004;Queck et al, 2006;Huang et al, 2007b;Case et al, 2008). For examples, the cross-domain communication by AHLs between bacteria in biofilms and spores of green alga Ulva indicated a direct function of AHLs in biofouling development (Joint et al, 2002).…”
Section: Dynamics Of Ahl-producing Bacteria During Subtidal Biofilm Fmentioning
confidence: 99%
“…This finding in the natural biofilm setting is in accordance with earlier studies in which the formation of grazing-resistant bacterial microcolonies in the presence of HF in the plankton was reported (Hahn & Höfle 1999, 2imek et al 2001. Subsequent laboratory studies on singlespecies bacterial biofilms have further shown that the formation of surface-attached microcolonies and consequently of bacterial biofilms was stimulated by the presence of HF (Matz et al 2004, Weitere et al 2005, Queck et al 2006.…”
Section: Top-down Effects Of Hf On Bacteriamentioning
confidence: 99%
“…Hall-Stoodley et al 2004). Recent experiments with single-species biofilms have shown that surface-associated microcolony formation is stimulated in the presence of potential protozoan grazers, and that they can resist high grazer densities (Matz et al 2004, Queck et al 2006. Nevertheless, this grazing resistance of bacterial microcolonies and biofilms is not a priori applicable to all protozoan types.…”
Section: Introductionmentioning
confidence: 99%